2022
DOI: 10.1017/s0007114522003968
|View full text |Cite
|
Sign up to set email alerts
|

How prevalent is a cancer-protective lifestyle? Adherence to the 2018 World Cancer Research Fund/American Institute for Cancer Research cancer prevention recommendations in Switzerland

Abstract: Population monitoring of lifestyle behaviors that are crucial as risk and protective factors for major chronic diseases is vital for the identification of priority areas for public health. In this study, we aimed to investigate the prevalence of adherence to the World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) cancer prevention recommendations in Switzerland, overall and by selected sociodemographic and lifestyle characteristics. Data from the population-based, cross-sectional surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 29 publications
4
6
0
Order By: Relevance
“…Our results regarding the determinants of adherence to a cancer-protective lifestyle are in agreement with the results in menuCH (Karavasiloglou et al, 2022) with a higher adherence among women than men and among participants with a tertiary than a secondary education level. The study by Lohse et al (2016) reported similar determinants as our study, showing that women, younger participants, Swiss nationals, not divorced or separated participants, and participants with a higher education level were more likely to be in the highest adherence category.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results regarding the determinants of adherence to a cancer-protective lifestyle are in agreement with the results in menuCH (Karavasiloglou et al, 2022) with a higher adherence among women than men and among participants with a tertiary than a secondary education level. The study by Lohse et al (2016) reported similar determinants as our study, showing that women, younger participants, Swiss nationals, not divorced or separated participants, and participants with a higher education level were more likely to be in the highest adherence category.…”
Section: Discussionsupporting
confidence: 90%
“…The median total score indicated an overall moderate adherence across the six SHS. Our results are comparable with those of the Swiss study that used data from the National Nutrition Survey menuCH (Karavasiloglou et al ., 2022) and the Swedish study (Kaluza et al ., 2020), in which most of the participants were categorized into the moderate adherence group (57.9% and 73.3%, respectively).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations